Electronic Fetal Monitoring of Low Risk Patients (Global Journal of Medical Research, 2020)
Introduction-Minimizing fetal morbidity during labor is one of the principal aims of intrapartum care. Electronic fetal heart rate monitoring (EFM) and intermittent auscultation are the known modalities of intrapartum fetal surveillance. Electronic fetal heart rate monitoring is routinely used at admission-the so-called Fetal Admission Test. If no fetal heart rate abnormalities are detected, continuous electronic monitoring is replaced by intermittent assessment for the remaining labor. The Admission test may help to identify those cases at risk in labor at the same time doing away with continuous monitoring. EFM at high risk is understandable, but at low-risk, does its advantages balance out the cost and increased incidence of operative delivery? This study is aimed at studying electronic fetal monitoring of low-risk patients in labor and its relation to perinatal outcome.